2018
DOI: 10.1111/ggi.13532
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive activity in a sitting position is protectively associated with cognitive impairment among older adults

Abstract: Aim Previous studies have obtained inconsistent results regarding the association between sedentary behavior and cognitive impairment. The present study aimed to examine the association between cognitive activity in a sitting position (CAS) and cognitive impairment among older adults. Methods Community‐dwelling older adults, from Obu or Nagoya in Japan, participated in a survey in 2013. A total of 5300 participants (mean age 75.0 ± 5.1 years; women 52.9%) met the criteria for the present study. We assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…This could be because the study assessed CA only by computer use, which was associated with a highly reduced odds ratio of MCI (OR: 0.50, 95% CI: 0.36-0.71) (21). Our research group has found that CA that occurs in the sitting position, such as reading books and computer use, is protective against cognitive impairment after adjustment for self-reported PA and sitting time (25).…”
Section: Discussionmentioning
confidence: 83%
“…This could be because the study assessed CA only by computer use, which was associated with a highly reduced odds ratio of MCI (OR: 0.50, 95% CI: 0.36-0.71) (21). Our research group has found that CA that occurs in the sitting position, such as reading books and computer use, is protective against cognitive impairment after adjustment for self-reported PA and sitting time (25).…”
Section: Discussionmentioning
confidence: 83%
“…These items were selected based on a review of other questionnaires. [10][11][12][13][14] Items (3) to (6) and (8) for ST with cognitive activity in Table 1 referred to activities with relatively high cognitive demand among 23 everyday activities according to the rankings of cognitive psychologists. 17 In addition to these activities, we added "driving a car," "paid or nonpaid work," and "using a computer or smartphone" to the items on ST with cognitive activity, as those who engage in these activities have high cognitive function.…”
Section: Methodsmentioning
confidence: 99%
“… 1 Although most research has found that excessive sedentary time (ST) is associated with adverse health outcomes, 2 some cohort studies reported a protective effect of sedentary behavior in specific settings on certain outcomes, especially mental health aspects such as cognitive function. 3 - 7 Recently, it has been suggested that sedentary behavior needs to be classified and reconsidered in detail by type (e.g., computer use [cognitively active] vs. watching TV [passive]). 1 In turn, evaluating not only total sedentary time (ST) but ST in specific settings can help to clarify its influence on older adults’ health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associations between various types of activities and health among older adults have therefore been intensively studied. Studies have shown that leisure-time, productive, social, and intellectual activities have positive effects on physical, mental, and cognitive health as well as life expectancy [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%